[ASr4Cl][Ge3S10] (A = Na, K) and [KBa4Cl][Ge3S10]: new salt-inclusion infrared nonlinear optical crystals with zero-dimensional [Ge3S9] clusters. Issue 22 (6th October 2022) - Song, Yufei; Cui, Shaoxin; Qian, Zhen; Yu, Hongwei; Hu, Zhanggui; Wang, Jiyang; Wu, Yicheng; Wu, Hongping
Abstract : Three new Salt-Inclusion Infrared Nonlinear Optical Crystals with Zero-dimensional [Ge3S9] Clusters. Abstract : Three new chalcohalide nonlinear optical crystals, [ASr4 Cl][Ge3 S10 ] (A = Na, K) and [KBa4 Cl][Ge3 S10 ], have been successfully designed and synthesized by combining the covalent [Ge3 S9 ] clusters and ionic [AB4 Cl] frameworks. Their crystal structures were determined by single crystal X-ray diffraction, which showed that all three compounds crystallized in the noncentrosymmetric and polar space group of P 63 . Three structures are iso-structural and can be seen as salt-inclusion structures with the isolated [Ge3 S9 ] clusters stacked alternately along the c axis and 1 ∞ [ClNaSr(2)3 ] 6+ chains acting as scissors to cut the connection between the [Ge3 S9 ] clusters, which is still rare in the known chalcohalides. The IR and Raman spectra indicate that [ASr4 Cl][Ge3 S10 ] (A = Na, K) and [KBa4 Cl][Ge3 S10 ] have wide IR transparent windows up to 20 μ m. UV-Vis-NIR diffuse reflectance spectra manifest that all three compounds have large band gaps of 3.54, 3.51, and 3.57 eV, respectively. In addition, the title compounds also exhibit large laser damage thresholds (∼12 × AgGaS2 ) and moderate SHG responses (1.08, 0.91, and 0.82 × AgGaS2, respectively). These properties demonstrate their potential as IR NLO crystals. Furthermore, the influence of the (M + N)/Q ratios (M = IIIA or IVA, N = IB or IIB or cations coordinated as [M x Q y ] anionic groups; Q = S, Se) on the anionic group structural dimensions was discussed, and the structure–property relationship was also studied based on the first-principles calculations. These may produce some insights for designing new chalcohalides.